Characterization and new applications of the acousto-optic effect in fiber gratings - Oliveira, Roberson Assis de (2011)
In this work, the fundamentals of the acousto-optic modulation in diffraction gratings are presented. By means of a detailed analysis of the mechanical excitation modes applied to the modulator set, it was noticed that two predominant modes of acoustic excitation can be found in the optical fiber depending on the applied acoustic frequency. Through this characterization, it was possible to develop new applications, such as a fast acousto-optic add-drop multiplexing for optical channels, which produces one of the fastest switching device presented in the literature, a narrow tunable single channel dispersion compensator, a tunable optical filter based on the acousto-optic modulation of a phase-shifted fiber Bragg grating, a new method to control the spectrum of Bragg gratings during the writing process and a viscosity sensor, whose application can be considered the most promising.